Microsatellite in Aeschynomene falcata (Leguminosae): diversity, cross-amplification, and chromosome localization - Polido, C. A.; Mantello, C. C.; Moraes, A. P. [UNESP]; Souza, A. P.; Forni-Martins, E. R. (Funpec-editora, 2014)
Aeschynomene falcata is an important forage species; however, because of low seed production, it is underutilized as forage species. Aeschynomene is a polyphyletic genus with a challenging taxonomic position. Two subgenera have been proposed, and it is suggested that Aeschynomene can be split in 2 genera. Thus, new markers, such as microsatellite sequences, are desirable for improving breeding programs for Aeschynomene falcata. Based on transferability and in situ localization, these microsatellite sequences can be applied as chromosome markers in the genus Aeschynomene and closely related genera. Here, we report the first microsatellite library developed for this genus; 11 microsatellites were characterized, with observed and expected heterozygosities ranging from 0.0000 to 0.7143 and from 0.1287 to 0.8360, respectively. Polymorphic information content varied from 0.1167 to 0.7786. The departure from Hardy-Weinberg equilibrium may have resulted from frequent autogamy, which is characteristic of Aeschynomene falcata. Of the 11 microsatellites, 9 loci were cross-amplified in Aeschynomene brevipes and Aeschynomene paniculata and 7 in Dalbergia nigra and Machaerium vestitum. Five of these 7 cross-amplified microsatellites were applied as probes during the in situ hybridization assay and 2 showed clear signals on Aeschynomene falcata chromosomes, ensuring their viability as chromosome markers.
Keywords: Cross-amplification; Fluorescence in situ hybridization; Forage; Microsatellite